BIPOLAR (T,S)-FUZZY MEDIAL IDEAL OF BCI-ALGEBAS - Samy Mohammed Mostafa; Abdelaziz Elazab Radwan; Amany El-menshawy; Reham Ghanem (Journal of New Theory)
In this paper, the concept bipolar (T,S)- fuzzy medial-ideals are introduced and several properties are investigated .Also, the relations between bipolar (T,S)- fuzzy medial-ideals and bipolar (T,S)- fuzzy BCIideals are given .The image and the pre-image of bipolar (T,S)- fuzzy medial-ideals under homomorphism of BCI-algebras are defined and how the image and the pre-image of bipolar (T,S)- fuzzy medial-ideals under homomorphism of BCI-algebras become bipolar (T,S)- fuzzy medial-ideals are studied. Moreover, the Cartesian product of bipolar (T,S)- fuzzy medial-ideals in Cartesian product BCI-algebras is established